2014
DOI: 10.1111/spc3.12099
|View full text |Cite
|
Sign up to set email alerts
|

The Police Officer's Dilemma: A Decade of Research on Racial Bias in the Decision to Shoot

Abstract: We review sociological, correlational, and experimental research that examines the effect of a target's race on the decision to shoot. Much of this work involves computer‐based simulations of a police encounter, in which a participant must decide whether or not to shoot a potentially hostile target who is either Black or White. Experimental work with undergraduate participants reveals a clear pattern of bias (a tendency to shoot Black targets but not Whites), which is associated with stereotypes linking Blacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 52 publications
2
109
0
1
Order By: Relevance
“…More generally, proenvironmental attitudes and intentions have been found to predict only a small part of the variance in actual sustainable behaviour (for a review, see Unsworth, Dmitrieva, & Adriasola, ). In interpersonal behaviour, much research has shown that implicit stereotypes, prejudice, and aggressive impulses can influence our behaviour despite egalitarian and nonaggressive intentions, especially when we cannot easily monitor and control the behaviour in question (e.g., Correll, Hudson, Guillermo, & Ma, ; Denson, DeWall, & Finkel, ; Derous, Nguyen, & Ryan, ; Dovidio, Kawakami, & Gaertner, ).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, proenvironmental attitudes and intentions have been found to predict only a small part of the variance in actual sustainable behaviour (for a review, see Unsworth, Dmitrieva, & Adriasola, ). In interpersonal behaviour, much research has shown that implicit stereotypes, prejudice, and aggressive impulses can influence our behaviour despite egalitarian and nonaggressive intentions, especially when we cannot easily monitor and control the behaviour in question (e.g., Correll, Hudson, Guillermo, & Ma, ; Denson, DeWall, & Finkel, ; Derous, Nguyen, & Ryan, ; Dovidio, Kawakami, & Gaertner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Racial disparities in seat belt enforcement are especially concerning because interactions with police can escalate, and blacks are more likely to be victims of police brutality than whites.19 Police killed Marlon Brown when he tried to evade a traffic stop for a seat belt violation.20 Levar Jones was unarmed when he was shot by a police officer while reaching for his license after a seat belt stop.21 Police shattered a window and tased Jamal Jones before they cited him for failing to wear a seat belt.22 David S. Cunningham iii, a 59-year-old judge, was handcuffed, detained, and searched after being stopped for a seat belt citation while leaving a parking lot.23 These men were all black, and their experiences reflect a more general pattern of racial bias in law enforcement. 24 Seat belt mandates also disproportionately burden poor people, if only because they cannot afford to pay the fees associated with a citation and they are more likely to face jail time or late penalties. This is especially troubling because poor people are already subject to greater domination from public officials and are more vulnerable relative to police, so seat belt mandates compound existing inequalities and patterns of domination.…”
Section: The Case Against Seat Belt Mandatesmentioning
confidence: 99%
“…Signal detection theory has been crucial to understanding the decision to shoot (Correll, Hudson, Guillermo, & Ma, 2014), as it allows differences in the respondent's sensitivity to the presence of a gun and their bias to shoot to be modeled separately.…”
Section: Statistical Analysesmentioning
confidence: 99%